(3OjhGf GdeJfHjs - (3CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeJfHj, CHh GdWjH, J (B354 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG aJM ef GdYhGQa hCdge ef GdeYGQa hChd TYQ GdOjhGf(B: (3Cpenf EROjGQc aj GdOLi GdoqQbHGA EP MjK cfJ ef GdXdGe VjGA s
(3BNQgG (B:s
(3hef LgdrJ faoSg bOQg QCi ZjoQg efg eG dG jQi s
(3GdfSNI HgG MhGTs
(3Ydi gPg GdfSNI RjGOGJ de JKHJ aj GdfSN GdeJOGhdI ef GdOjhGfs
(3QGLY UaMGJ (B264 (3, (B278 (3, (B300s
(3fSNI QGHYI hHghGeTgG TQhM cKjQI hbO UOQJ GdbUGFO HGdefGSHGJ ceG CfgG oeQJHI Ydi MQha GdoeYLe Ydi WQjbI GdeZGQHIs
(3eY ebOeI dCHj LeYI GdeQGcTj s
(3hQO CjVoG JMJ Qbe (B873s
Keywords: (3GdCOHs